Studi Perbandingan Return Saham Perusahaan Perbankan dan Perusahaan Pertambangan di Bursa Efek Indonesia - Endah Tri Wahyuningtyas; Mardiyah Anugraini (Jurnal Bisnis dan Keuangan, 2019)
This research was conducted to answer investors’ doubts in investing their capital in the stock market, the large number of stock sectors offered in the stock market made investors have to analyze properly before deciding which sector of the stock promises the greatest profit and has the best growth. In this study the author tries to compare between the stock returns of the banking and financial sector in Indonesia securities. And the results of the research can be concluded that the stock returns of banking companies are based on capital gains higher than mining companies.